Pengaruh pendidikan kewirausahaan dan motivasi terhadap minat berwirausaha mahasiswa Prodi Pendidikan Ekonomi Universitas Negeri Surabaya - Oktiena, Shaskya Wida; Dewi, Retno Mustika (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze (1) the partial effect of entrepreneurship education on interest in entrepreneurship, (2) entrepreneurial motivation on interest in entrepreneurship, and (3) the simultaneous influence of entrepreneurship education and entrepreneurial motivation on interest in entrepreneurship of students of the UNESA Economics Education Study Program. The research used is correlational (associative) with a quantitative approach. The study used primary data obtained from questionnaires. The method of analysis used multiple linear regression analysis. The object of research is the 2017-2019 Unesa Economics Education Study Program students with a sample of 135 students. The study results show that entrepreneurship education has a significant effect on interest in entrepreneurship, entrepreneurial motivation has a significant effect on interest in entrepreneurship, and entrepreneurship education and entrepreneurship motivation simultaneously have a significant and positive effect on students' interest in entrepreneurship. Â